Narrative Reciprocity - Charon, Rita (The Hastings Center report, 2014)
I have become curious about reciprocity within clinical practice. A vast topic that mobilizes considerations of money, knowledge, kinship, power, culture, and uses of the body, reciprocity is a strong means by which to achieve the egality required of just health care. Within health care, reciprocity might enable not only so-called shared decision-making and patient autonomy. It might open the door to mutual acknowledgement of the value of each participant's beliefs and habits. It might appear as a humble realization that no one understands what health is and a concurrent welcoming curiosity about one another's conception of how the body and speech and mind work. From the intimate to the international levels of care, such forms of reciprocity may culminate in the radical and powerful state of reciprocal recognition. In this short essay, I will focus on one aspect of reciprocity in health care: the narrative and potentially reciprocal nature of attention in health care. A critical element in the development of therapeutic alliance, clinical accuracy, and effective practice, attention requires a donation of the self as a vessel into which can enter that which is perceived or, from the other side, a penetrating of that which is perceived so that one sees it from within its own vessel.